Photosensitization of Bioinspired Thymine-Containing Polymers - Martino, Debora Marcela (2008)
Here, we report a sensitization study on a family of water-soluble photopolymers based on thymine. The goal of this study was to determine whether the presence of sensitizer molecules would promote photocrosslinking/immobilization of the polymers using low-energy irradiation (520 nm) as compared to the UV irradiation (approximately 280 nm) necessary for the standard photoinduced process to take place. With the aid of Eosin Y Spirit Soluble (EY) as a sensitizer, water-soluble polystyrene copolymers of vinylbenzylthymine-vinylbenzyltriethylammonium chloride (VBT-VBA) were immobilized after exposure to visible irradiation. By exciting the sensitizer molecule in the presence of VBT copolymers at a wavelength where absorption by the latter does not occur, the triplet state of the sensitizer is generated in high yields, and consequently, polymer photocross-linking takes place. UV-vis spectroscopy has been used to study the effect of irradiation dose, copolymer composition, and sensitizer concentration on the photoreactivity of VBT polymers. These studies demonstrate the feasibility of using Eosin Y as a sensitizer to achieve the thymine photodimer formation, resulting in immobilization of VBT-VBA-EY films on PET substrate. This provides complementary information on photoinduced immobilization of VBT-VBA films that are crucial for developing new classes of environmentally benign materials and new energy-saving methods.